The motor rhythm and its impact on the development of performance on the balance beam in gymnastics for the second stage students For the evening study (Journal of the College of Basic Education, 2022)
The research consisted of five chapters, including the first chapter, which highlights the impact ofThe use of some means of aesthetic education to assist in learning, such as rhythmic movement. It appears importantResearching the identification of better teaching methods that help in the development of female students and qualify them inovercoming the difficulty of their performance. The second chapter included two main axes. The first included studiesTheory As for the second axis, it included previous and similar studies, as the researcher presented a previous study